Determination of Sex by various Morphometric Traits of Clavicle in the population of Central India (Bhopal region) - Anuradha Singh; Rajendra Baraw; Jayanthi Yadav (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Identification is the determination of the individuality of a person based on certain physical characteristics. The clavicle is one of the bones which is less explored but has drawn considerable interest in this field, particularly concerning sexual dimorphism. Aim& Objectives: The present study evaluates the existence of sexual dimorphism based on various morphometric parameters of the clavicle in a dry sample and identifies the best predictor amongst these. Materials & Methodology: The study was conducted in the mortuary of the Department of Forensic Medicine, Gandhi Medical College, Bhopal on 100 random cases (50 males;50 females) in which medico-legal post-mortem examination was done. After taking due consent, clavicle bone of deceased between25 to 60 years age group were collected during the autopsy, dried and then examined for the study. Measurements were carried out and statistically compared to evaluate sexual dimorphism. The studied parameters include Maximum length of clavicle, Breadth of sternal end, Breadth and Length of acromial end, Area of acromial surface and Mid clavicular circumference. Observations & Results: Amongst all the parameters, Maximum length of clavicle and Mid clavicular circumference are the most reliable parameters for sexual dimorphism with 81% accuracy rate when considered together. If all the morphometric parameters are taken together then the sex can be determined with 87% accuracy. Conclusion: Sexual dimorphism exists in clavicle and all the measured parameters contribute to different sex individually and with 87% accuracy when taken together. The derived discriminant function equations can be used to correctly assign the bones to the proper sex.